The Impact Of FDI To The ICT Industry: A Comparative Study Between Malaysia And Korea - Hamzah, Niza Adila (2001)
This paper examines whether the inflow of foreign dircet investment (FDI) has an impact to the host country economy particularly in the Information and Communication Technology (ICT) industry. The discussion focuses on two countries, Malaysia and Korea. It has been designed to include companies with business operation related with ICT products and services.